Oxidative balance score and its association with chronic inflammatory airway diseases and mortality: a population-based study - Luo, Zhuanbo; Chen, Shiyu; Chen, Peixu; Qiu, Feng; Huang, Weina; Cao, Chao (Frontiers in Nutrition, 2025)
ObjectiveThe aim of this research was to explore the possible connection between combined Oxidative Balance Score (OBS) and the prevalence of chronic inflammatory airway diseases (CIAD), including asthma, chronic obstructive pulmonary disease (COPD), and chronic bronchitis, along with the mortality rate among individuals with CIAD.MethodsData were gathered from the National Health and Nutrition Examination Survey (NHANES) 2013–2018 cycles. The Oxidative Balance Score (OBS) was calculated using 16 different nutrients and 4 different lifestyles, which was then categorized into four groups. The CIAD included individuals with self-reported asthma, chronic bronchitis, or COPD. Mortality data up to December 31, 2019, was obtained from the National Death Index. In cross-sectional studies, the association between OBS and the prevalence of total and specific CIAD was examined using multiple logistic regressions. Dose–response relationships were analyzed through restricted cubic spline regression (RCS). In prospective cohort studies, cumulative survival rates were determined using the Kaplan–Meier method and compared with log-rank tests. Multiple COX regressions were conducted to evaluate the relationship between OBS and all-cause as well as respiratory diseases mortality among participants with CIAD.ResultsA total of 12,458 adults were enrolled in this study. The demographic characteristics of the study population revealed a mean age of 52.25 ± 15.8 years, 47.73% being male, and the majority identified as Non-Hispanic White (66.87%). We found that 20.26% of the participants were suffered from CIAD, followed by asthma (15.41%), chronic bronchitis (6.10%) and COPD (3.80%), respectively. The median OBS levels were 20.98 with a standard deviation of 0.17. After adjusting for all confounders, we found that the highest quartile of OBS was significantly associated with lower prevalence of total CIAD (OR = 0.71, 95% CI 0.64–0.81), asthma (OR = 0.62, 95% CI 0.52–0.73), chronic bronchitis (OR = 0.64, 95% CI 0.44–0.92), and COPD (OR = 0.48, 95% CI 0.31–0.77) compared to the lowest quartile. Additionally, a linear and inverse relationship was found between OBS and the incidence of various respiratory disorders. Kaplan–Meier survival analysis showed that individuals in the highest quartile of OBS had the lowest risk of both all-cause mortality (log-rank test p = 0.017) and respiratory diseases mortality (log-rank test p < 0.001). Furthermore, after adjusting for multiple factors, individuals in the fourth quartile continued to show a significantly reduced risk of all-cause mortality (HR = 0.71, 95% CI 0.55–0.93) and respiratory diseases mortality (HR = 0.53, 95% CI 0.43–0.74) in comparison to those in the lowest quartile of OBS levels.ConclusionThe findings revealed that a higher OBS was significantly linked to a decreased prevalence of total and specific CIAD, including asthma, chronic bronchitis, and COPD. Higher OBS levels were also associated with reduced mortality from both all causes and respiratory diseases among CIAD patients. These findings offer valuable information on the role of diet and lifestyle in preventing CIAD.